Effects of Online Learning on the Communication Skills of BSED 3rd Year Social Science Major at Bestlink College of the Philippines A.Y. 2021 - 2022: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Online Learning is Education that takes place over the internet. It is often referred to as "e-learning", among other terms. However, online learning is only one type of "distance learning", the umbrella term for any learning across distance, not in a traditional classroom.  Communication skills are the set of activities that involve listening, speaking, emphasizing, and observing to achieve a great understanding. These skills are crucial to expressing the speaker's point of view and ideas. In addition, for the communication process, teachers are responsible for giving knowledge and information to the receiver and assuring that they acquire those facts needed for their academics. Communicating strengthens the excellent connection between students and instructors, leading to attaining the same goals during online learning.  We all know that online learning attracts more students for better learning experiences. However, many of them encountered challenges that can hinder their learning. These are the problems that students encountered:  Adaptability, technical issues, computer knowledge, time management, self-motivation, and communication.   The researchers used the descriptive method design to complete the study. The proponent selected thirty (30) students from the 3rd year level currently enrolled in Bachelor of Secondary Education major in Social Science at Bestlink College of the Philippines who have experienced online learning and responded to the online survey questionnaire related to our study. The researcher utilized the purposive sampling technique to determine the target population of those in the study. It obtained the desire of thirty (30) students to know the effects of online learning on the communication skills of Bachelor of Secondary Education majors in 3rd year Social Science majors.